PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS - Usman Aprian; Ahmad Junaidi (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2022)
This study aims to determine whether cash turnover and receivable turnover have effects on profitability. The research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This study used a purposive sampling method, with the number of 55 companies each year, therefore the total sample is 165. The statistical method uses multiple linear regression analysis with t statistics hypothesis testing. The results of this study state that cash turnover has a significant positive effect on profitability. That states, company’s effectivity in managing its cash to generate revenue or sales is very impressive. Contrariwise, receivable turnover has a negative and significant effect on profitability. That states, high levels of receivable can reduce the profitability because the amount of receivable owned is small, which means the credit sales made are low, thus sales volume and profitability will decrease as well.